Protective Effects of Lovastatin in a Population‐Based ALS Study and Mouse Model. Issue 5 (30th January 2023) - Kreple, Collin J.; Searles Nielsen, Susan; Schoch, Kathleen M.; Shen, Tao; Shabsovich, Mark; Song, Yizhe; Racette, Brad A.; Miller, Timothy M.
Abstract : Objective: The objective of this study was to use a novel combined pharmacoepidemiologic and amyotrophic lateral sclerosis (ALS) mouse model approach to identify potential motor neuron protective medications. Methods: We constructed a large, population‐based case‐control study to investigate motor neuron disease (MND) among US Medicare beneficiaries aged 66 to 90 in 2009. We included 1, 128 incident MND cases and 56, 400 age, sex, race, and ethnicity matched controls. We calculated MND relative risk for >1, 000 active ingredients represented in Part D (pharmacy) claims in 2006 to 2007 (>1 year before diagnosis/reference). We then applied a comprehensive screening approach to select medications for testing in SOD1 G93A mice: sulfasalazine, telmisartan, and lovastatin. We treated mice with the human dose equivalent of the medication or vehicle via subcutaneous osmotic pump before onset of weakness. We then assessed weight, gait, and survival. In additional mice, we conducted histological studies. Results: We observed previously established medical associations for MND and an inverse dose–response association between lovastatin and MND, with 28% reduced risk at 40 mg/day. In SOD1 G93A mouse studies, sulfasalazine and telmisartan conferred no benefit, whereas lovastatin treatment delayed onset and prolonged survival. Lovastatin treated mice also had less microgliosis, misfolded SOD1, and spinal motor neuron loss in the ventral horn. Interpretation: Lovastatin reduced the risk of ALS in humans, which was confirmed in an ALS mouse model by delayed symptom onset, prolonged survival, and preservation of motor neurons. Although further studies to understand the mechanism are required, lovastatin may represent a potential neuroprotective therapy for patients with ALS. These data demonstrate the utility of a combined pharmacoepidemiologic and mouse model approach. ANN NEUROL 2023;93:881–892